Education Complements Health Status of Households in Kerala: A Study of Malappuram District - Ibrahim Cholakkal and Dr. N. Radhakrishnan (IOSR Journal Of Humanities And Social Science (IOSR-JHSS), 2014)
Health is a persistent source of education development and social welfare of a nation. There is unpredictable qualitative and quantitative association between education and health. This paper is generated from the pilot survey results of the research works of the authors. In this paper the researchers assess about the link between education and health by stating two objectives: to examine the status of education and health of people in Kerala and to analyse the influence of education and other individual characteristics on the health status of households. A multiple regression model has been applied for the analysis of data. An education index is constructed by taking the actual years of formal education of individuals ages 23 and above since they have most likely already be completed their formal education. For the construction of aggregate health index (AHI), the researchers have framed nine other health indices namely, Physical Environment Index (PEI), Life Style Disease Index (LSDI), Consumption Index (CMPNI), Intoxicant Abuse Index (IAI), Health Awareness Index (HAI), Maternal Health Index (MHI), Health Maintaining Index (HMI), Individual Hygiene Index (IHI) and Nutritious Food Index (NFI). This paper exhibits that there is an improvement in the education and health status of people of Kerala during the analysis period of seven decades. Education has a positive significant association on the health status of households. Income of the households is negatively related with health status in the study area since, higher income households diagnose their health problems and reported it properly. Age status is negatively related with health status of households. The sex ratio and the year of marriage are positively associated with level of education.